Kampus Merdeka Sebagai Wadah Pengembangan Metode Mengajar Yang Kreatif Melalui Pendekatan Kampus Mengajar Untuk Memperkuat Literasi Numerasi Dan Teknologi Di Smp Al-Huda Surabaya - Marta Uli Septiana Manalu; Cholis Hidayati (Universitas Kristen Indonesia Toraja, 2023)
Independent Learning-Independent Campus is a policy of the Minister of Education and Culture which encourages students to study various fields in order to enter the world of work. The Independent Learning-Campus Independent Policy is guided by Permendikbud Number 3 of 2020 concerning Higher Education National Standards. Students as